Special issue problematizing prostitution: critical research and scholarship - Hail-Jares, Katie; Leon, Chrysanthi S.; Shdaimah, Corey S.; Sarat, Austin (Bingley, U.K. : Emerald, 2016)
The scholars who contribute to this issue utilize diverse research methods to examine the lived experiences of people engaged in prostitution and the people and institutions that process them. They look at the production of knowledge about prostitution and trafficking by institutional stakeholders, and how legal responses to prostitution and trafficking are affected by class, race, ethnicity, and migration. Drawing on data derived from innovative research methods including auto-ethnography, re-calculation of historical data, and participatory methods, the authors challenge us to re-examine the pro-sex/abolitionist divide, the historical theories of prostitution and ethical concerns around research with people engaged in prostitution. Instead our authors offer new configurations of sex, gender, and prostitution to better inform future scholarship, policy, and programming.
Sex worker or student? Legitimation and master status in academia / Jenny Heineman -- "In my head, I didn't feel like I had done anything wrong": women's experiences prostituting women and girls / Mahri Irvine -- Relationships among stigmatized women engaged in street-level prostitution: coping with stigma and stigma management / Corey Shdaimah, Chrysanthi S. Leon -- Reform or remand? race, nativity, and the immigrant family in the history of prostitution / Anne E. Bowler, Terry G. Lilley, Chrysanthi S. Leon -- Inevitably violent? Dynamics of space, governance and stigma in understanding violence against sex workers / Teela Sanders -- Bad dates: how prostitution strolls impact client-initiated violence / Katie Hail-Jares -- Unionizing sex workers: the Karnataka experience / Subadra Panchanadeswaran, Gowri Vijayakumar, Shubha Chacko, Andy Bhanot.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy -- Social Policy; Law & society; Prostitution; Prostitution -- Law and legislation